Guidelines for reporting case studies and series on drug-induced QT interval prolongation and its complications following acute overdose. (2nd January 2020) - Berling, Ingrid; Hatten, Benjamin W.; Hoffman, Robert S.; Othong, Rittirak; Roberts, Darren M.; Mustafa, Reem A.; Yates, Christopher; Cormier, Monique; Gosselin, Sophie
Abstract: Background: The assessment and management of patients with QT interval prolongation in poisoning requires an appropriate method of measuring and adjusting the QT interval for the heart rate (HR) in order to decide if the patient is at risk of life-threatening dysrhythmias, notably torsade de pointes (TdP). As the Clinical Toxicology Collaborative (CTC) workgroup reviewed the published literature on drug-induced QT interval prolongation in poisoning, it became obvious that many publications were missing essential data that were necessary to thoroughly assess and compare the evidence. The aim of this guidance document is to identify essential and ideal criteria required when reporting a case of drug-induced QT interval prolongation and/or TdP in poisoning. Methods: We employed a mixed methods approach as follows. Initially, we reviewed 188 cases of available published case reports and series in the literature regarding drug-induced QT interval prolongation and/or TdP in poisoning as the first step to another project. Common features and deficiencies were identified. Given the large gaps in reporting quality, we conducted an iterative consultative process involving all 23 members of the CTC to identify essential and ideal criteria to analyse publications of QT interval prolongation in poisoning. A priori standards were developed for acceptance or rejection of individual criteria. Results: Survey response was 100%. A minimum set of essential criteria for reporting cases of QT interval prolongation and drug-induced TdP in overdose setting are provided and a 35-item checklist is presented. Conclusions: We report a QT reporting checklist to ensure published case reports and series describing drug-induced QT interval prolongation in poisoning can contribute to the fund of knowledge of QT interval prolongation, TdP and other malignant dysrhythmias.